Yona of the dawn. 29 - Kusanagi, Mizuho, 1979-; MacFarlane, Ysabet Reinhardt (Shojo beat manga., 2021)
"Princess Yona lives an ideal life as the only princess of her kingdom. Doted on by her father, the king, and protected by her faithful guard Hak, she cherishes the time spent with the man she loves, Su-won. But everything changes on her 16th birthday when tragedy strikes her family!... King Kuelbo of North Kai plans to attack Kohka, with the goal of capturing the Dragon Warriors! When Yona and Jaeha are kidnapped and forced to go to Kai, Hak considers befriending the enemy of his enemy -- joining the Kohka army!"--Provided by publisher.